Growing of thallium-doped KDP and ADP crystals: structural and optical parameters - Salo, V.I.; Tkachenko, V.F.; Voronov, A.P.; Puzikov, V.M.; Tsurikov, V.A. (Functional Materials, 2005)
Studied has been the influence of thallium activator on the growth kinetics and structure perfection of KDP and ADP crystals, the character of its incorporation and distribution in the crystal lattice and the photoluminescence properties. Revealed has been thallium incorporation anisotropy in the prism and pyramid growth sectors of ADP crystals which may be caused by the charge state of the {100} and {101} growth planes. For KDP crystals, thallium incorporation is limited by the ionic radii difference of the K⁺ and Tl⁺ cations. Doping with thallium in amounts up to 1.0 mass % causes no changes in the structure perfection of KDP and ADP crystals. Thereat, for ADP crystals, there the increase of the lattice parameter а by 0.9-⁻³ ± 3-10⁻⁵ А is revealed and the decrease of the parameter с by 1.1-10⁻³±3-10⁻⁵ А. The thallium absorption band in KDP:TI⁺ and ADP:TI⁺ crystals lies near 220 nm, emission band maximum is at 280 nm. Вивченo вплив активатора талiю на кiнетику росту та структурну досконалiсть кристалiв KDP та ADP, характер входження i розподiлу його у кристалiчнiй гратцi та на фотолюмiнесцiйнi властивостi. Виявлено анiзотропiю входження домiшки талiю у сектори росту призми та пiрамiди кристалiв ADP, що може бути обумовлено зарядовим станом площин росту {100} i {101}. У кристалах KDP входження домiшки талiю лiмiтується вiдмiннiстю йонних радiусiв катiонiв K⁺ і Tl⁺. При легуваннi талiєм До 1,0 мас.% кристалiв KDP i ADP змiнення структурної досконалостi не встановлено. При цьому виявлено збiльшення параметра гратки а на 0.9-⁻³ ± 3-10⁻⁵ А та зменшення параметра с на 1.1-10⁻³±3-10⁻⁵ А для ADP кристалiв. Смуга поглинання талiю у кристалах KDP:TI та ADP:TI знаходиться у межах 220 нм, а максимум смуги емiсiї знаходиться на довжинi хвилi 280 нм. Изучено влияние активатора таллия на кинетику роста и структурное совершенство кристаллов KDP и ADP, характер вхождения и распределение его в кристаллической решётке и на фотолюминесцентные свойства. Обнаружена анизотропия вхождения примеси таллия в секторы роста призмы и пирамиды кристаллов ADP, что может быть обусловлено зарядовым состоянием плоскостей роста {100} и {101}. В кристаллах KDP вхождение примеси таллия лимитируется различием ионных радиусов катионов K⁺ и Tl⁺. При легировании таллием до 1.0 масс.% кристаллов KDP и ADP изменения структурного совершенства не установлено. При этом обнаружено увеличение параметра решётки а на 0.9-⁻³ ± 3-10⁻⁵ А и уменьшение параметра с на 1.1-10⁻³±3-10⁻⁵ А для ADP кристаллов. Полоса поглощения таллия в кристаллах KDP:TI⁺ и ADP:TI⁺ лежит в области 220 нм, максимум полосы эмиссии приходится на 280 нм.